KINERJA PENYULUH AGAMA NON PNS KEMENTERIAN AGAMA - Hamzah, Ali (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2018)
Abstract: Abstract: In addition, Islamic religious instructors in carrying out their duties and functions are assisted by non-civil servants of Islamic religious instructors consisting of religious leaders who are very instrumental in fostering religious communities to improve the faith, piety and harmony of religious people, especially in Sungai Penuh City. The formulation of the problem in this study is how the performance of the Non government employees Religious Extension Ministry of Religion (Study in Sungai Penuh City). This research is a qualitative research with a type of field research. Data collection techniques used include observation, interviews and documentation studies. In this study the author did the processing in several ways as follows: 1) data reduction (data reduction); 2) selecting data; 3) data analysis; 4) data presentation (data display); and 5) draw conclusions. The results of this study include: 1) the standard of performance of Non government employees religious instructors in the office of the Ministry of Religion in Sungai Penuh prioritized by a Bachelor of Religion Higher Education diploma, domiciled in the city of Sungai Penuh and having a built village; 2) performance criteria consist of 6 types, namely: quality, quantity, timeliness, cost effectiveness, need for supervision and interpersonal impact; and 3) the motivation given by the Ministry of Religion of Non government employees in the office of the Ministry of Religion of Sungai Penuh City consists of 2, namely: intrinsic motivation and extrinsic motivation.